Clinicopathological Findings of Retinoblastoma: A 10-Year Experience from a Tertiary Hospital in Kampala, Uganda - James Joseph Yahaya; Belson Rugwizangoga; Alex Mremi; Asafu Munema (Journal of Ophthalmology)
Background. Retinoblastoma (RB) is one of the most common cancers occurring in young children in sub-Saharan Africa. The incidence rate reported in the literature is 9,000 new cases per year, which corresponds to 1 in 15,000 births. This study aimed at analyzing the clinicopathological findings in children with RB in Uganda. Purpose. The purpose of this study was to describe and analyze the clinicopathological findings in the patients with RB. Design. This was a cross-sectional analytical study involving 234 eyeball surgical specimens from 214 patients with RB diagnosed between January 2006 and December 2015. Results. The mean age of the patients was 27.8 months (SD = 21.413, range: 1–132 months). More than half of the cases, 50.9%, presented with leucokoria. Invasion of choroid, sclera, anterior chamber, and optic nerve was found in 26.5% (n = 58), 51.2% (n = 88), 26.2% (n = 45), and 29.2% (n = 49), respectively. Twenty-six percent (n = 56) of the cases with intraocular tumour were at stage I and all patients with metastasis 4.7% (n = 11) had stage IV. The correlation between postlaminar optic nerve invasion and massive choroidal invasion was statistically significant (P=0.002). Also, there was a statistical significance difference between metastasis and postlaminar invasion (P=0.004). Conclusion. The majority of children with RB in Uganda present clinically with leucokoria, and their parents or guardians seek medical intervention at a later stage. Moreover, there was a noticeably significant lag period for the patients to begin treatment after the diagnosis was done.